2021
DOI: 10.1142/s2010135x21500120
|View full text |Cite
|
Sign up to set email alerts
|

Improved ferroelectric and piezoelectric properties of (Na0.5K0.5)NbO3 ceramics via sintering in low oxygen partial pressure atmosphere and adding LiF

Abstract: Dense ([Formula: see text][Formula: see text]NbO3 lead-free ceramics with the simple composition were prepared via sintering in low oxygen partial pressure (pO2, [Formula: see text][Formula: see text] atm) atmosphere and adding LiF. All the ceramics have pure orthorhombic structure. Compared to the LiF-added ([Formula: see text][Formula: see text]NbO3 ceramics sintered in air and the low pO2-sintered pure ([Formula: see text][Formula: see text]NbO3 ceramics without LiF addition, the present ceramics exhibit im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, when the sample was subjected to double calcination and sintering, the deviations in KNN stoichiometry might occur due to uneven volatilization of the alkali oxides (Na2O and K2O) takes place as a result of their relatively high volatility [6] due to twice calcination and milling. It is suggested that to achieved a pure orthorhombic phase of KNN with higher densification, the sintering atmosphere should be controlled as this sintering atmosphere could affect the existence of oxygen vacancies in KNN based ceramics [14,15].…”
Section: (B) Sinteringmentioning
confidence: 99%
“…Therefore, when the sample was subjected to double calcination and sintering, the deviations in KNN stoichiometry might occur due to uneven volatilization of the alkali oxides (Na2O and K2O) takes place as a result of their relatively high volatility [6] due to twice calcination and milling. It is suggested that to achieved a pure orthorhombic phase of KNN with higher densification, the sintering atmosphere should be controlled as this sintering atmosphere could affect the existence of oxygen vacancies in KNN based ceramics [14,15].…”
Section: (B) Sinteringmentioning
confidence: 99%
“…In the case of base metals as electrodes, low oxygen partial pressure (pO 2 ) atmosphere is always needed to prevent oxidization of base metal electrodes if the annealing temperatures are relatively high. Structure and electrical properties of K 0.5 Na 0.5 NbO 3 ceramics are closely related to the processing atmospheres of low pO 2 25,26 . Up to now, there are few reports about CSP followed by post‐annealing in low pO 2 atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Structure and electrical properties of K 0.5 Na 0.5 NbO 3 ceramics are closely related to the processing atmospheres of low pO 2 . 25,26 Up to now, there are few reports about CSP followed by post-annealing in low pO 2 atmospheres.…”
Section: Introductionmentioning
confidence: 99%